2018
DOI: 10.1007/s00261-018-1574-4
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic neuroendocrine tumor: review of heterogeneous spectrum of CT appearance

Abstract: PanNETs are typically hypervascular and have avid enhancement on arterial and venous phase images. However, dedicated pancreas protocol may be needed due to their sometimes atypical appearance including transient enhancement. Careful evaluation of CT findings will help differentiate PanNETs from their mimics, and can be used to establish the diagnosis of a PanNETs. Although an accurate diagnosis can be based on serological, urine, and CT scan findings, confirmation is made via pathological examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Several studies have shown that, beyond these solid structural components, vascularization and perfusion also contribute to the stiffness of biological tissues [12,15,35,36]. High tumor vascularization, which is particularly characteristic of neuroendocrine tumors [7], might thus also contribute to their greater stiffness. To the best of knowledge, only one study so far has analyzed PNET stiffness in a subgroup of seven participants using single-frequency MRE [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that, beyond these solid structural components, vascularization and perfusion also contribute to the stiffness of biological tissues [12,15,35,36]. High tumor vascularization, which is particularly characteristic of neuroendocrine tumors [7], might thus also contribute to their greater stiffness. To the best of knowledge, only one study so far has analyzed PNET stiffness in a subgroup of seven participants using single-frequency MRE [13].…”
Section: Discussionmentioning
confidence: 99%
“…Multidetector computed tomography (MDCT) can contribute to discriminate between different pancreatic neoplasms [5]. PNETs often present as solid, well-circumscribed masses with contrast-enhancement in CE-CT and CE-MRI [6,7]. Somatostatin-receptor-specific imaging using PET/CT/PET/MRI provides NET-specific functional information on somatostatin-receptor expression and density with high diagnostic performance.…”
Section: Introductionmentioning
confidence: 99%
“…These lesions show avid enhancement in arterial and venous phase CT because of rich intralesional vascularity. 3 On MRI, most functioning PanNETs are hypointense on T1W and hyperintense on T2W images and show intense and early enhancement on dynamic T1W sequence after contrast injection.…”
Section: Discussionmentioning
confidence: 98%
“…Absent such biochemical indicators, the clinical management of pancreatic NETs is primarily stage-guided by Ki67 index and mitotic count observed in tissue samples obtained by biopsy; however, imaging characteristics, such as tumour size, depth of invasion and presence of metastases, are also considered 63 66 . Pancreatic NETs classically present on CT imaging as contrast-enhancing masses that are best visualized on the arterial phase, often with a hypervascular appearance and washout on the delayed phase 67 , 68 .…”
Section: Diagnosticsmentioning
confidence: 99%
“…Pancreatic adenocarcinoma is an exocrine malignancy of the epithelioid ductal cells that often confers a poor prognosis due to delays in diagnosis 80 , 81 . Although pancreatic NETs are usually distinguishable from adenocarcinomas on CT by their vascularity pattern and absence of ductal dilation, a hypovascular enhancement pattern occurs non-infrequently in atypical variants 63 , 67 , 68 . To date, statistical approaches utilizing histogram analysis on CT images have seen conflicting findings in terms of the robustness of features used for differentiation, including entropy, kurtosis and skew 82 , 83 .…”
Section: Diagnosticsmentioning
confidence: 99%